Commuting Quasihomogeneous Toeplitz Operator and Hankel Operator on Weighted Bergman Space. (28th July 2013) - Yang, Jun
Abstract : We characterize the commuting Toeplitz operator and Hankel operator with quasihomogeneous symbols. Also, we use it to show the necessary and sufficient conditions for commuting Toeplitz operator and Hankel operator with ordinary functions.